The Influence of Transformational Leadership on the Performance of Food Security, Agriculture, and Fisheries Service Employees in Nias Regency - Oliziduhu Halawa; Isfenti Sadalia; Janita S. Meliala (PT FORMOSA CENDEKIA GLOBAL, 2023)
Leadership is very influential on activity and continuity in organizations, so leadership is one key to success in organizations. Leaders who aren't competent in anticipating and deliver response fast to change will cause organization slow for adapt change so that employee No will Once increase with optimal. The type of research is study quantitative. Study quantitative is data research in form the numbers obtained from respondent. Population in study This is whole Food Security, Agriculture and Fisheries Service Employees Regency Nias as many as 65 people. Questionnaire study given direct to respondent with choose one alternative answers that have available. Statement customized with need study with using a Likert Scale. In research this, method analysis used is method descriptive quantitative. This show that variable leadership transformational influential positive by 38.6%, p This can determined based on R Square value of 0.386 and significant to performance staff at the Department of Food Security , Agriculture and Fisheries Regency Nias.